VENEZUELAN MIGRATION FROM THE COLOMBIAN PERCEPTION WITH ONTO-AXIOLOGICAL CRITERIA - Maldonado , Nilson (Revista Arbitrada Formación Gerencial, 2024)
The central purpose of the article is to interpret Venezuelan migration from the Colombian perception with an onto-axiological criterion from the City of Riohacha Municipality La Guajira Colombia. It was oriented under a qualitative research approach, considering the Interpretive Paradigm through the Phenomenological method. The actors under study are 4 citizens from the City of Riohacha, and 4 Venezuelan citizens who are based in said context. It was a field work, through participatory observation and in-depth interview. Information is presented through of statements, bullets and matrices. The techniques used to gather information are demonstrated by means of external validity and reliability, categorizing the position of the key informants to generate a new theory that allowed presenting final reflections, thereby highlighting that Venezuelan migration occurs in the face of a political crisis affecting the Venezuelan who decides to migrate with the interest of improving her quality of life; However, in the case studied, the Colombians showed that they saw the Venezuelan as people who came to take away their work spaces, even generating scenarios of xenophobia, affecting an open and respectful cultural relationship.